Cascade testing as the missing link in cancer prevention among Lynch syndrome families - Lea Godino; Giulia Erini; Giovanni Innella; Sara Miccoli; Simona Ferrari; Pamela Magini; Luca Caramanna; Martina Preite; Veronica Simoni; Daniela Turchetti (Familial Cancer, 2026)

Fatal dengue virus infection in an unvaccinated traveler - Jonathan Steinke; Veronica Di Cristanziano; Jan-Hendrik Naendrup; Dániel Cadar; Martin Gabriel; Roger Grosser; Noëlle Sieg; Lisa Altenrath; Jesko Welters; Alexander Simonis; Rosanne Sprute; Jorge Garcia Borrega; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Dengue is an increasing threat to individuals living in or visiting endemic countries. Effective vaccines have become available, but their use in travelers is typically only recommended to individuals with documented prior infection. We present a fatal case of severe dengue in an unvaccinated traveler without known prior dengue virus infection but longitudinal serologic and molecular evidence for secondary infection. In the context of this case and vaccination guidance for travelers, we discuss pre-vaccination screening, potential implications for travelers to regions with ongoing outbreaks, and emphasize the importance of serostatus-independent vaccines.

Microplastics in urban water cycles: Looking for a more scientific approach for sampling and characterization in wastewater and drinking water treatment plants - Alessia Foglia; Lucia Pittura; Veronica Vivani; Massimiliano Sgroi; Lucia De Simoni; Anna Laura Eusebi; Stefania Gorbi; Francesco Regoli; Francesco Fatone (Science of The Total Environment, 2024)